Formal methods in dynamic software updating: a survey. (19th March 2019) - Lounas, Razika; Mezghiche, Mohamed; Lanet, Jean-Louis
Dymanic software updating (DSU) consists in updating running programs on-the-fly without any downtime that leads to systems unavailability. The use of DSU in critical applications raises several issues related to update correctness. Indeed, an erroneous dynamic update may introduce safety vulnerabilities and security breaches. In this perspective, the use of formal methods has gained a large interest since they respond to the high need of rigor required by such applications. Several frameworks were developed to first express update correctness which is based on several criteria. Then, the proposed formalisms are used to specify DSU systems, express correctness criteria and establish them. In this paper, we present a review of researches on the application of formal methods to DSU systems. We give a classification of systems according to the paradigms of programming languages and then we explain the correctness criteria and categorise the articles regarding the approaches of formalisation to establish the correctness. This information is useful to help ongoing researches in having an overview on the application of formal methods in DSU.